Understanding the use of the National Early Warning Score 2 in acute care settings: a realist review protocol - Nia Roberts; Geoff Wong; Michelle Treacy; Mandy Odell (BMJ Open)
Introduction Failure to recognise and respond to patient deterioration in an appropriate and timely manner has been highlighted as a global patient safety concern. Early Warning Scores (EWSs) using vital signs were introduced to address this concern, with the aim of getting the patient timely and appropriate treatment. The National Early Warning Score 2 (NEWS2) is in use across the NHS, and many other settings globally. While patient improvements have been shown, research has identified that the NEWS2 is not always used as intended. Therefore, this review will use a realist approach to understand what the mechanisms are that influence appropriate use (or not) of the NEWS2 in acute care settings, how, for whom and in which contexts. The findings will inform clinicians of what helps and/or hinders appropriate use of the NEWS2 in clinical practice, thus helping to facilitate successful implementation.Methods and analysis Our realist review will follow Pawson’s iterative six step process: (1) Development of initial programme theory. (2) Searching the literature; an information scientist will develop, pilot and refine the search strategy. A systematic search will be completed, based on subject relevancy on the following databases: Cumulative Index to Nursing and Allied Health Literature (CINAHL), Medline, Embase (OvidSP), Web of Science (Science Citation Index and Social Science Citation), Cochrane Database of Systematic Reviews, Joanna Briggs Institute, Ethos, Proquest Dissertations and Theses Global, and Google Scholar for documents dating from 1997 (date of the first published EWS) to present. To retrieve additional relevant data ‘snowballing’ (finding references and authors by hand, contacting authors, searching reference lists and citation-tracking using Google Scholar) will be used. Inclusion criteria include all documents (including grey literature) that relate to the use of EWSs/NEWS2 in the English language only. Documents set in the paediatric, maternity and primary care settings will be excluded. (3) Selecting documents and quality appraisal. (4) Extracting and organising the data. (5) Synthesising the data. (6) Disseminating the findings. We will recruit a group of stakeholders comprised of experienced clinicians who use the NEWS2 as part of their clinical practice to provide feedback throughout the review. Step 1 has already begun with the development of an initial programme theory. This initial programme theory presents how the NEWS2 is supposed to work (or not), it will now be developed, tested and refined.Ethics and dissemination Ethical approval is not required for this study as it is secondary research. Dissemination will include a peer-reviewed publication and conference presentations. Findings will also be amplified through social media platforms with user friendly summaries. Our stakeholder group will also contribute to dissemination of findings in their clinical areas and among existing networks.PROSPERO registration number CRD42022304497.